Self-regulated learning strategies in reading comprehension of a group of ESL students / Bromeley Philip - Philip, Bromeley (Universiti Teknologi MARA Cawangan Kedah, 2018)
This study was aimed at ascertaining the degree to which ESL students use Self-regulated learning (SRL) strategies which include planning, monitoring, problem solving and evaluating. It was also aimed at assessing the degree of awareness on the part of the students of their selfefficacy beliefs in using self-regulated strategies. The study was conducted on a group of ESL students at a public university in Sarawak within 30 hours of reading class whereby the students were exposed to the four self-regulated strategies. Direct Explanation Method was used to teach students on using SRL strategies. The research employed a mixed method incorporating both quantitative and qualitative paradigms. However, due to the limitation of the paper, only the quantitative aspect of the study is highlighted. The data were collected using likert-type inventories and immediate written recall protocols generated through semi-structured interviews. The findings reveal that the students were using the strategies frequently throughout their reading process with the exception of Evaluating strategy, which was hardly being used. The findings also show that the students were confident of their ability in using the strategies as they reported high score on the self-rating self-efficacy scale. This study has to a certain extent provided some interesting evidence on the nature of learning the students were involved in especially as regards the use of SRL strategies.